Status does not predict stress: Women in an egalitarian hunter–gatherer society. (24th August 2020) - Fedurek, Piotr; Lacroix, Laurent; Lehmann, Julia; Aktipis, Athena; Cronk, Lee; Townsend, Cathryn; Makambi, E. Jerryson; Mabulla, Ibrahim; Behrends, Volker; Berbesque, J. Colette
Abstract: Abstract: It is widely believed that there is strong association between physiological stress and an individual's social status in their social hierarchy. This has been claimed for all humans cross-culturally, as well as in non-human animals living in social groups. However, the relationship between stress and social status has not been explored in any egalitarian hunter–gatherer society; it is also under investigated in exclusively female social groups. Most of human evolutionary history was spent in small, mobile foraging bands of hunter–gatherers with little economic differentiation – egalitarian societies. We analysed women's hair cortisol concentration along with two domains of women's social status (foraging reputation and popularity) in an egalitarian hunter–gatherer society, the Hadza. We hypothesized that higher social status would be associated with lower physiological indicators of stress in these women. Surprisingly, we did not find any association between either foraging reputation or popularity and hair cortisol concentration. The results of our study suggest that social status is not a consistent or powerful predictor of physiological stress levels in women in an egalitarian social structure. This challenges the notion that social status has the same basic physiological implications across all demographics and in all human societies.